Stabilization and Resuscitation of Newborns - Schwaberger, Bernhard (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The majority of newborns do not need medical interventions to manage the neonatal transition after birth. However, every year millions of newborns worldwide require respiratory support immediately after birth, and another considerable number of newborns additionally require extensive resuscitation including chest compressions and drug administration. Despite a significant increase in knowledge and development of enhanced therapy strategies over the past few years, morbidity and mortality caused by failures in neonatal transition remain an important health issue. The purpose of this reprint is to support or introduce novel concepts and add information in the area of the "Stabilization and Resuscitation of Newborns", aiming to improve neonatal care and, as the major objective, to enhance neuro-developmental outcomes.